Response of the Soil Microbe Community to Maize Residue Management Strategies Under Double-Cropping Systems - Gao, Fei; Zhang, Chao; Gao, Zheng; Zhang, Jiwang (Frontiers in Agronomy, 2022)
Sustainable agriculture has become a common trend in countries around the world. This includes returning straw to the field as part of sustainable crop production. However, it is not known whether changing the amount of straw returned to the field will lead to changes in the microbial community during decomposition and subsequent nutrient use by the next season’s crop. The design included three treatments: 1) all the summer maize stalks returned to the field (SR); 2) half the summer maize stalks returned to the field (HSR); and 3) no summer maize stalks returned to the field (control: CK), base on all the winter wheat stalks were returned to the field. Compared with CK, the annual yield of SR treatment and HSR treatment increased by 18.8% and 17.3%, respectively. However, there are no significant difference in crop yield between the SR and HSR treatments. Compared with CK, the Proteobacteria increased by 29.9% in SR and 31.2% in HSR, which is the second most common bacterium during the maturity stage of maize season. Different crops season have an important impact on soil microbial community function (ANOSIM, R = 0.5209, P = 0.001). The PCoA analysis of the Faprotax function prediction found that the functional composition in the wheat planting period (wheat jointing and wheat harvest) was more similar, and the functional composition of maize planting period (maize tasseling and maize harvest) was more similar. The HSR can significantly increase the diversity of species in the soil to meet the nutritional demands for crop growth for achieve high and stable crop yield.